A Proposed Program for Training Social Science Teachers in High Schools in the Kingdom of Saudi Arabia - Sami Mohammed Milhem (Journal of Educational Sciences, 1991)
The problem of this research can be outlined as follows: Designing a program for training social science teachers in high schools in the Kingdom of Saudi Arabia (K.S.A.). This research will study some important and fundamental elements in the educational system in K.S.A. it focusses on how to improve the competency of social science teachers in high schools in order to improve the process of effective teaching. This study is confined to teaching competencies which are needed for an effective social science teaching in high schools in K.S.A. It does not include other professional or academic (subject matter) competences. This study is divided in two parts including the derivation of the bases and procedures used in competency derivation in general, and, in particular. the frame of reference for the derivation of the competencies used for this research. it was derived from the following three major sources: (a) objectives of social teaching in high schools, (b) specifications of effective social sciences’ teaching in high schools; (c) management and teaching duties of social science teachers in high school. Discussion of teaching strategies used in competency-based teacher education program. This research offered a pattern for a training program aiming at developing the competencies of social science teachers in evaluating student learning of social sciences, and providing the opportunity for social science teachers in high schools in K.S.A. to study the organization of units which were constructed in this research and to apply this research‘s findings in revising the programs of teaching social sciences at the girls colleges in K.S.A.